External human–machine interfaces: Gimmick or necessity?. (September 2022) - de Winter, Joost; Dodou, Dimitra
Highlights: External human–machine interfaces (eHMIs) have received lots of attention. This paper reviews arguments for and against eHMIs. This work is hoped to advance the debate on the necessity of eHMIs. Abstract: The last few years have seen a wealth of research on external human–machine interfaces (eHMIs). It has been argued that eHMIs are vital because they fill the social interaction void that arises with the introduction of automated vehicles (AVs). However, there is still much discussion about whether eHMIs are needed. The present article surveys arguments for and against eHMIs. We list three arguments against eHMIs: (1) Implicit communication dominates pedestrian-AV interaction, and there is no social interaction void to be filled, (2) There is a large variety of eHMI concepts and a lack of standardization and consensus, and (3) eHMIs may elicit various negative effects such as distraction, confusion, and overreliance. Next, we present five reasons why eHMIs may be useful or required: (1) eHMIs can make planned actions of the AV visible, thereby increasing the efficiency of pedestrian-AV interaction, (2) Participants value an eHMI compared to no eHMI, (3) eHMIs do not have to be limited to showing instructions or the AV's planned actions; showing the AV mode or the AV's cooperative or detection capabilities are other uses of eHMIs, (4) Recent research shows that driver eye contact is important in traffic, and a social interaction void thus exists, and (5) A large portion of pedestrian-vehicle accidents in current traffic is caused by unclear implicit communication, suggesting that pedestrians may benefit from explicit eHMIs. It is hoped that this article contributes to the critical discussion of whether eHMIs are needed and how they should be designed.